EFFECT OF HYPNOTEACHING METHOD ON LEARNING MOTIVATION OF PAI STUDENTS - Lilik Maftuhatin; Deva Ihtiyarina; Dhikrul Hakim; Dwi Nurcahyani (Universitas Negeri Surabaya, 2026)
Hypnoteaching is an instructional method that engages students' subconscious mind through suggestion, relaxation, and various hypnotic techniques to foster meaningful communication between teachers and learners. This quantitative correlational study examined the effect of the hypnoteaching method on the learning motivation of Islamic Religious Education (PAI) students at Universitas Pesantren Tinggi Darul Ulum Jombang. Data were collected from 75 semester VI students through observation, documentation, and questionnaires, then analyzed using a percentage formula and Pearson product-moment correlation with the assistance of SPSS. The results showed that the implementation of the hypnoteaching method reached a percentage score of 77.2%, while students' learning motivation reached 67.5%, both falling within the good category. Correlation analysis yielded a coefficient of 0.306 with a significance value of 0.007, below the 0.05 threshold, leading to the rejection of H0 and the acceptance of Ha. This result was further confirmed by comparing the calculated r-value with the critical r-value at the 0.05 significance level (0.306 > 0.227). Although statistically significant, the correlation was weak-to-moderate in strength, accounting for approximately 9.4% of the variance in learning motivation. These findings indicate that the hypnoteaching method contributes meaningfully to learning motivation among PAI students, though its effect should be interpreted alongside other factors that also influence student motivation in this setting.